2012
DOI: 10.1016/j.ijrobp.2012.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Integrated Boost Irradiation After Breast-Conserving Surgery: Physician-Rated Toxicity and Cosmetic Outcome at 30 Months’ Follow-Up

Abstract: Toxicity and CO are not impaired after 3D-CRT-SIB. Fibrosis was not significantly associated with radiotherapy parameters. Independent risk factors for fibrosis were chemotherapy after radiotherapy, re-resection, and larger tumor size. Re-resection was most predictive for worse CO. Age had an impact on chest wall pain occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 20 publications
(30 reference statements)
2
39
0
2
Order By: Relevance
“…36,39,43,50,53,55,56 However, the results from these studies were consistent with the results from studies amenable to pooling. We used the IASP criteria for the definition of persistent pain in this review; however, 14 of the included studies did not report whether their assessment of persistent postsurgical pain excluded other causes of pain; 26,[33][34][35][36]43,45,47,48,50,51,54,56,58 as such, they may have overestimated the prevalence of persistent pain.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…36,39,43,50,53,55,56 However, the results from these studies were consistent with the results from studies amenable to pooling. We used the IASP criteria for the definition of persistent pain in this review; however, 14 of the included studies did not report whether their assessment of persistent postsurgical pain excluded other causes of pain; 26,[33][34][35][36]43,45,47,48,50,51,54,56,58 as such, they may have overestimated the prevalence of persistent pain.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…5-year local control was 98.9% [36]. Regarding toxicity and cosmetic outcome, after a median follow-up time of 30 months (range 6-54 months), 8.5% of patients had ≥ G2 fibrosis in the boost area, chest wall pain was detected in 6.7%, and teleangiectasia was detected in 3.7% (≥ G2) [37]. Half of the patients developed all-grade fibrosis outside the tumor bed.…”
Section: Boosting the Tumor Bedmentioning
confidence: 99%
“…skin, subcutaneous tissue, ribs [9]). This topic was addressed by Bantema-Joppe et al [1] who recently reported their experience with the SIB technique in a publication that prompted the present editorial. Between 2005 and 2010, 940 patients were treated by standardfractionated WBI (28 fractions of 1.8 Gy) and SIB regimen of 2.3-2.4 Gy.…”
Section: Statement Of the German And The Austrian Societies Of Radioomentioning
confidence: 91%